MDX‐1097 induces antibody‐dependent cellular cytotoxicity against kappa multiple myeloma cells and its activity is augmented by lenalidomide. (3rd February 2015) - Asvadi, Parisa; Cuddihy, Andrew; Dunn, Rosanne D.; Jiang, Vivien; Wong, Mae X.; Jones, Darren R.; Khong, Tiffany; Spencer, Andrew
Summary MDX‐1097 is an antibody specific for a unique B cell antigen called kappa myeloma antigen (KMA) that consists of cell membrane‐associated free kappa light chain (κFLC). KMA was detected on kappa human multiple myeloma cell lines (κHMCLs), on plasma cells (PCs) from kappa multiple myeloma (κMM) patients and on κPC dyscrasia tissue cryosections. In primary κMM samples, KMA was present on CD38+ cells that were CD138 and CD45 positive and/or negative. MDX‐1097 exhibited a higher affinity for KMA compared to κFLC and the latter did not abrogate binding to KMA. MDX‐1097‐mediated antibody‐dependent cellular cytotoxicity (ADCC) and in vitro exposure of target cells to the immunomodulatory drug lenalidomide resulted in increased KMA expression and ADCC. Also, in vitro exposure of peripheral blood mononuclear cells (PBMCs) to lenalidomide enhanced MDX‐1097‐mediated ADCC. PBMCs obtained from myeloma patients after lenalidomide therapy elicited significantly higher levels of MDX‐1097‐mediated ADCC than cells obtained prior to lenalidomide treatment. These data establish KMA as a relevant cell surface antigen on MM cells that can be targeted by MDX‐1097. The ADCC‐inducing capacity of MDX‐1097 and its potentiation by lenalidomide provide a powerful rationale for clinical evaluation of MDX‐1097 alone and in combination with lenalidomide.